Adiabatic Two-Phase Flow Patterns for Zeotropic Mixtures of Tetrafluoromethane/Ethane in a Horizontal Smooth Tube. Issue 1 (March 2020) - Song, Q L; Chen, G F; Wang, H C; Deng, Z; Shen, J; Gong, M Q
Abstract: Mixed-refrigerant Joule-Thomson refrigeration (MJTR) systems have distinct advantages in the temperature range from 80 to 230 K. Tetrafluoromethane (R14) and ethane (R170) are essential components of mixed-refrigerants. Heat transfer and pressure drop for twophase flow are closely related to corresponding flow patterns. In this paper, an experimental investigation on adiabatic twophase flow patterns for R14/R170 mixtures in a horizontal smooth tube with inner diameter of 4 mm was presented. Experiments were carried out at mass fluxes from 100 to 350 kg m −2 s −1 and saturation pressures from 1.5 to 2.5 MPa over the entire range of vapor quality. The effects of concentration, mass flux, saturation pressure and vapor quality were analyzed and discussed. Furthermore, the observed flow patterns were compared with six existing flow pattern maps. Our previous model developed for pure R14 shows the best predictive ability with 80.16% of the data points can be accurately predicted.